About Preliminary Constitutional Control in Russian Federation - Machmutovna Khurmatullina, Alsu (2021)
The article analyzes the amendments to the Constitution that were adopted on July 4, 2020. The authors consider the changes concerning the legal status of the constitutional justice body in the Russian Federation and the Russian Federation subject. The article analyzes the foreign experience of exercising the powers of these bodies to exercise preliminary constitutional control and the possibility of their power use in Russian judicial practice.